An analysis of the intestinal microbiome combined with metabolomics to explore the mechanism of how Pangxiejiao tea improves metabolic disorders in HFFD-treated rats - Wang, Wanchun; Zhu, Enzheng; Yang, Yang; Huang, Qingqing; Xiao, Xue; Piao, Shenghua (Frontiers in Nutrition, 2025)
IntroductionThe high-fat and high-fructose diet (HFFD) can lead to various metabolic disorders. Pangxiejiao (PXJ), a natural plant widely used in folk practices, has been found to contain bioactive compounds that exhibit hypoglycemic effects in vitro. However, the potential of PXJ aqueous extract to ameliorate metabolic disorders in vivo and its underlying mechanisms remain unexplored. This study aims to investigate the effects of PXJ on metabolic disorders induced by HFFD in rats.MethodsAn HFFD was employed to mimic unhealthy dietary habits, while PXJ was administered via oral gavage for 10 weeks. Perform biochemical assays, observe histopathological structures, and evaluate metabolic status in rats to investigate intrinsic alterations through detection of gut microbiota and plasma metabolites.ResultsThe results demonstrated that PXJ intervention reduced body weight, improved glucose and lipid metabolism, and decreased serum uric acid levels. PXJ alleviated oxidative stress and inflammation, as evidenced by reduced serum levels of IL-1β, IL-6, and TNF-α, along with ameliorated pathological inflammatory manifestations in metabolism-related organs, such as liver, pancreas, and colon. Furthermore, PXJ was found to decrease the Firmicutes/Bacteroidota ratio, modulated gut microbiota composition, and maintain microbial homeostasis. Nontargeted metabolomics analysis identified 39 upregulated metabolites, including hippuric acid, and 9 downregulated metabolites, such as LysoPG(18:2(9Z,12Z)/0:0). Correlation analysis further revealed that PXJ maintains metabolic homeostasis through complex network crosstalk. Specifically, four gut microbial taxa including Alloprevotella and six metabolites, including hippuric acid, demonstrated significant negative correlations with IL-6, TNF-α, and MDA. In contrast, Lachnospiraceae_NK4A136_group showed positive correlations with these metabolites and SOD.DiscussionIn conclusion, early and sustained PXJ intervention alleviates HFFD-induced metabolic disorders, which is associated with restored gut microbiota balance, improved metabolism, and reduced inflammation and oxidative stress, demonstrating its potential as a novel functional tea for metabolic disorder prevention.